2016
DOI: 10.1007/s11626-016-0023-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of pluripotency markers in Arbas Cashmere goat hair follicle stem cells

Abstract: In our previous work, we found that the Inner Mongolia Arbas Cashmere goat hair follicle stem cells (gHFSCs) can be successfully differentiated into adipocyte, chondrocyte, and osteocyte lineages. In this study, we further examined the expression of the pluripotency and stemness markers Oct4, Nanog, Sox2, AKP, and TERT in gHFSCs by immunocytochemistry, flow cytometry, real-time PCR, and Western blot. Immunofluorescent staining showed that the gHFSCs were positive for all five markers. Fluorescence-activated ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Skin cells would then tend to overproliferate, which may provide an explanation for UVB-induced skin cancer. He et al showed that the expression of Nanog in goat hair follicle stem cells (gHFSCs) was higher than that in goat adipose-derived stem cells (gADSCs), indicating that the stemness and pluripotency of gHFSCs was stronger than that of gADSCs [26]. We suggest that downregulation of Nanog after grafting of ADSCs may reduce the stemness and pluripotency of skin stem cells and promote differentiation in related cell repair injuries.…”
Section: Discussionmentioning
confidence: 75%
“…Skin cells would then tend to overproliferate, which may provide an explanation for UVB-induced skin cancer. He et al showed that the expression of Nanog in goat hair follicle stem cells (gHFSCs) was higher than that in goat adipose-derived stem cells (gADSCs), indicating that the stemness and pluripotency of gHFSCs was stronger than that of gADSCs [26]. We suggest that downregulation of Nanog after grafting of ADSCs may reduce the stemness and pluripotency of skin stem cells and promote differentiation in related cell repair injuries.…”
Section: Discussionmentioning
confidence: 75%
“…HAP stem cells differentiate to multiple types of cells HAP stem cells differentiate to multiple types of cells: nerve cells including, adipocytes, glial cells, keratinocytes, smooth muscle cells, cardiac muscle cells, melanocytes, osteocytes and chondrocytes. 19,20 Moreover, HAP stem cells can regenerate the epidermis. The differentiation potential of HAP stem cells is greatest in the upper part of the follicle, which can produce large amounts of these stem cells (Fig.…”
Section: Discovery Of (Hap) Stem Cellsmentioning
confidence: 99%
“…A number of laboratories have performed gene-expression analysis on the hair-follicle stem cells, identifying stem-cellrelated gene expression, such as nestin, Nanog, OCT4, Sox-2 as well as differentiation markers 19,34 including human hair follicles stem cells. 35 The gene-expression data are complimentary to the immunohistochemistry data describe above.…”
Section: Issuesmentioning
confidence: 99%
See 2 more Smart Citations